Penyuluhan gizi pada ibu dengan menggunakan flip chart di kecamatan benua kayong Kabupaten ketapang - Uliyanti; Adha Panca Wardanu (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The aim of this Community service activities is to increase knowledge and understanding as well as mother participation in stunting prevention and early detection programs for children under five who are expected to their children's growth and development so that their growth and development can be optimized. The method used is to assess people's knowledge and the problems faced regarding prevention and how to assess / early detection of stunting in infants in Suka Baru village, Benua kayong subdistrict, Ketapang. Mother's knowledge was measured using pre-test before the activity and post-test after being given knowledge. Results showed pre test of participants high knowledge of the category were 2 people (3.08%), then after the post test increased to 11 people (16.92%), while participants low nutritional knowledge of the category were 4 people (6.15%) decreased to 1 person (1.54%). Based on these results, it is known that nutrition extension to mothers using flip chart able given increase nutrition knowledge 1.58%.